Respostas

2013-08-06T21:03:16-03:00
A) x(x+1)=30
x²+1x=30
x²+1x-30

b) x²+2.(x+1)=5
x²+2x+2=5
x²+2x+2-5=0
x²+2x-3=0

c) 2x.(4x-2)-4=0
8x²-4x-4=0

d) (6x+2)² -16=0
(6x+2).(6x+2)-16=0
36x²+12x+12x+4-16=0
36x²+24x-12=0

E agora é só usar a formula de Bhaskara.
a) x(x + 1)=30
x²+1x=30 x²+x-30=0Delta = 1²-4.1.-30Delta = 1 -+ 120Delta = 121x= -(1) +- Raiz de 121 / 2.1x= -1+11/2 = 10/2 = 5x" = -1-11/2 = 12/2 = 6
x² + 2 . (x+1)=5x² + 2x + 2 - 5 =0x² +2x - 3=0Delta= (2)² - 4.1.-3Delta = 4-4.-3Delta= 4+12Delta= 16x=-(2)+- raiz de 16 / 2.1 = -2+-4/2x= -2+4/2 = 2/2=1x"= -2-4/2 = -6/2=-3
2x(4x-2)-4=08x²-4x-4=0Delta = (-4)²-4.8.-4Delta= 16-32.-4Delta=16+128Delta= 144x=-(-4)+- raiz 144/2.8 =4+-12/16 = 4+12/16=16/16=14-12/16= 8/16 = 0,5
(6x+2)²-16=036x+4-16=036x=0+16-436x-4=12x=12/36